2022
DOI: 10.1126/sciadv.abq1700
|View full text |Cite
|
Sign up to set email alerts
|

Facet-selective etching trajectories of individual semiconductor nanocrystals

Abstract: The size and shape of semiconductor nanocrystals govern their optical and electronic properties. Liquid cell transmission electron microscopy (LCTEM) is an emerging tool that can directly visualize nanoscale chemical transformations and therefore inform the precise synthesis of nanostructures with desired functions. However, it remains difficult to controllably investigate the reactions of semiconductor nanocrystals with LCTEM, because of the highly reactive environment formed by radiolysis of liquid. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…We used in-situ liquid-phase TEM to reveal the moisture-induced degradation mechanism of quantum-sized semiconductor nanocrystals (Figure c). Because of the limitations stated in the introduction, previous works have focused on the etching processes controlled by the radiolysis products of the electron beam. ,,, To overcome this limitation, we developed advanced liquid cells (graphene double-liquid-layer cells) that allow control of the initiation of chemical reactions during atomic-resolution liquid-phase TEM; their fabrication process and working mechanism are discussed in the next section. Figure d and Video S1 reveal the representative reaction stages of the moisture-induced degradation process of CdS quantum nanorods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used in-situ liquid-phase TEM to reveal the moisture-induced degradation mechanism of quantum-sized semiconductor nanocrystals (Figure c). Because of the limitations stated in the introduction, previous works have focused on the etching processes controlled by the radiolysis products of the electron beam. ,,, To overcome this limitation, we developed advanced liquid cells (graphene double-liquid-layer cells) that allow control of the initiation of chemical reactions during atomic-resolution liquid-phase TEM; their fabrication process and working mechanism are discussed in the next section. Figure d and Video S1 reveal the representative reaction stages of the moisture-induced degradation process of CdS quantum nanorods.…”
Section: Resultsmentioning
confidence: 99%
“…In-situ liquid-phase transmission electron microscopy (TEM) can directly visualize structural changes in individual nanocrystals with high spatial (sub-nanometer) resolution. The control over the reactions of nanocrystals during liquid-phase TEM is usually limited to electron-beam-induced reactions. Reactions of noble metal nanocrystals induced by radiolysis products are representative examples of these works. , Microfabricated cells can be modified to flow-type cells, such that the initiation of the reaction can be controlled by regulating the introduction of chemicals through inlets (Figure S1). , However, effective imaging is challenging because of strong electron beam scattering by thick liquid layers (typically >100 nm) , and unwanted sample movement caused by the liquid flow.…”
mentioning
confidence: 99%
“…≈ 30 nm -50 nm, with 50 nm being the most common in order to provide robustness at the expense of electron beam transparency 50 . As a result, a large portion of the high-resolution LCEM work is nowadays relying on the encapsulation and formation of small pockets of liquid between two ultrathin membranes made of amorphous carbon 51,52 , graphene [29][30][31][32][33][34][35][36][37] , or their combination with SiNx to produce hybrid NFCs 40,41 . Among these choices, graphene cells (GCs) [29][30][31][32][33][34][35]37 have become the standard to achieve atomic resolution in LCEM experiments.…”
Section: Mainmentioning
confidence: 99%
“…The recent development of liquid cell transmission electron microscopy (LCTEM) has made it possible to observe the dynamic changes of nanomaterials in liquid in real time with high temporal and spatial resolution. Thus far, LCTEM technology has been applied to many fields ranging from materials science to chemistry, physics and biology, such as nanocrystal growth, [21][22][23][24] dissolution, [25][26][27] self-assembly, 28 phase transformation, 29 nanobubble formation, 30,31 electrochemical reactions, 32,33 and bioscience. 34 For the etching of ZnO, recently, Sun et al observed the formation of hillocks on the (0001 ˉ) O-terminated surface of ZnO nanobelts during in situ etching by in situ LCTEM and experimentally demonstrated the micro-mask mechanism.…”
Section: Introductionmentioning
confidence: 99%